2020
DOI: 10.11591/ijict.v9i2.pp117-139
|View full text |Cite
|
Sign up to set email alerts
|

Cloud computing survey on services, enhancements and challenges in the era of machine learning and data science

Abstract: <p>Cloud computing has sweeping impact on the human productivity. Today it’s used for Computing, Storage, Predictions and Intelligent Decision Making, among others. Intelligent Decision Making using Machine Learning has pushed for the Cloud Services to be even more fast, robust and accurate. Security remains one of the major concerns which affect the cloud computing growth however there exist various research challenges in cloud computing adoption such as lack of well managed service level agreement (SLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 21 publications
(24 reference statements)
0
23
0
Order By: Relevance
“…The completed cloud computing infrastructure design provides customers with network security, uninterrupted services, and high bandwidth using the Internet. Figure 2 illustrates the generic cloud architecture which includes the main components of cloud computing, mainly: infrastructure, storage, service, application, management, and security [2]. Cloud computing systems can be divided into two parts: the front end and the back end, and both are connected and can be accessed via the Internet.…”
Section: Cloud Computing Architecturementioning
confidence: 99%
See 2 more Smart Citations
“…The completed cloud computing infrastructure design provides customers with network security, uninterrupted services, and high bandwidth using the Internet. Figure 2 illustrates the generic cloud architecture which includes the main components of cloud computing, mainly: infrastructure, storage, service, application, management, and security [2]. Cloud computing systems can be divided into two parts: the front end and the back end, and both are connected and can be accessed via the Internet.…”
Section: Cloud Computing Architecturementioning
confidence: 99%
“…SaaS is a software delivery model by which a fully functional subscription-based model is delivered online to the customers, where the end customer can usually access SaaS offers online. Figure 4 shows the responsibility and management of the cloud customer and the CSP that manage various components of the offering SaaS [2].…”
Section: Models Of Cloud Computing Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Figure 1 shows the different components of the Cloud Computing Architectural Framework. The discussion of each component of the architectural framework is out of scope of this paper however it has been discussed in detail in the following paper [24].…”
Section: Cloud Computing Architectural Frameworkmentioning
confidence: 99%
“…This model will continue to study every transaction data that occurs so that the number of orders to suppliers will be optimal. Several recent studies [35]- [37] have suggested that machine learning is needed to get a simple and more accessible method by downloading experiment simulation data packages and creating intelligent decision making [38]- [42] have suggested that machine learning proves the ability of computer algorithms to improve performance over time, handle data more efficiently, select relevant features and power system reliability. Machine learning can improve performance by modeling the transients in the switches, one of which is the agricultural sector [43], [44].…”
Section: Introductionmentioning
confidence: 99%